Implementasi Metode Menghafal Al-Qur'an 3T + 1M pada Rumah Tahfidz Se Kabupaten Tanah Datar - Zulfan Ependi; Asnelly Ilyas; Suharmon Suharmon; Iman Asroa B.S (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This study aims to explain the planning, implementation and evaluation as well as the obstacles in applying the 3T+1M method for memorizing the Qur'an in Tahfidz houses throughout Tanah Datar Regency. This research is based on the existence of the 3T+1M method used at the Tahfidz house in Tanah Datar Regency which has a positive impact on students. The research was conducted using field research methods to collect data at the research location. The research was conducted using a qualitative approach by presenting an overview of the application of the 3T+1M method at Tahfidz's house, Tanah Datar Regency. The research was conducted from January to July 2022. The data sources were teachers and students in 12 Tahfidz houses in Tanah Datar Regency who applied the 3T+1M method. Data collection is done by observation, interviews and documentation. The results of the research show that 1) Planning is done by making memorization targets, making Al-Qur'an memorization programs and making a schedule of activities; 2) Implementation is carried out by applying the Tikrar, Tafahhum, Tasmi', and Muraja'ah methods; 3) Evaluation of implementation by asking students to repeat memorization, reciting memorization, and depositing memorization and strengthening it in the evaluation of Tafhidz's book as a report and basis for follow-up learning; and 4) various obstacles in the form of immature student ages, debates over students' comprehension, coercion and low student motivation, and not being able to read the Qur’an or not being fluent in reading the Qur’an.